THE CONCEPT OF CLIMATE RESILENT ECONOMY: UZBEKISTAN (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Since climate change is a worldwide concern, Uzbekistan's climate-economic relationship study is evaluated in respect to other nations. The concept of climate change resilient economy is summarized in this study article. The findings show that Uzbekistan is making headway toward greater preparedness for future detrimental effects of the climate change, even in light of the country's precarious position with relation to it.